1994
DOI: 10.1002/nt.2620020504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen concentration and cold temperature on DSP‐toxin concentrations in the dinoflagellate Prorocentrum lima (prorocentrales, dinophyceae)

Abstract: The diarrhetic shellfish poisoning toxin-producing dinoflagellate, Prorocentrum lima, isolated from Nova Scotian waters, contained both okadaic acid (OA) and dinophysistoxin-1 (DTX-1) throughout its growth cycle in culture; maximum concentrations of toxins and highest OA/DTX-1 ratios occurred during the stationary phase. Cells of P. lima survived 0 degrees C for 5 weeks and recovered when brought to a higher temperature. During the cold period, some cell damage probably occurred with concomitant losses of toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
3
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 10 publications
6
44
3
5
Order By: Relevance
“…Nevertheless, it was important to ascertain that the strain of P. lima collected from the field site was indeed toxigenic. The cellular toxin levels detected in the field material agree well with published values for cultured P. lima isolated from this site (McLachlan et al 1994). There are, however, noteworthy differences between the toxin profile of an isolate (Strain Pa) previously cultured from this site and that of the bulk field samples collected in this study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, it was important to ascertain that the strain of P. lima collected from the field site was indeed toxigenic. The cellular toxin levels detected in the field material agree well with published values for cultured P. lima isolated from this site (McLachlan et al 1994). There are, however, noteworthy differences between the toxin profile of an isolate (Strain Pa) previously cultured from this site and that of the bulk field samples collected in this study.…”
Section: Discussionsupporting
confidence: 85%
“…There are, however, noteworthy differences between the toxin profile of an isolate (Strain Pa) previously cultured from this site and that of the bulk field samples collected in this study. The cultured isolate of P. lima from Indian Point was found to produce relatively high amounts of OA, and significantly lower concentrations of DTX1 (McLachlan et al 1994) than contained in the field samples reported here. The high DTX1/OA ratio detected in the bulk epiphytic material is the first report that corresponds to the profile found in mussels collected from the Indian Point site in 1990, after human cases of shellfish poisoning (Quilliam et al 1993).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Thus, while copepods may act as vectors of DSP toxins to higher trophic levels, the amount of these toxins that copepods transport in the food web may be limited (Kozlowsky-Suzuki et al, 2006). Dinoflagellate cell toxicity varies widely with environmental conditions (McLachlan et al, 1994;Morton et al, 1994), between species and strains (Lee et al, 1989), and with habitat and life cycle (Pan et al, 1999;Souto et al, 2001), but it is not clear how this variation in OA production influences its ecological effects and community-level impacts.…”
Section: Okadaic Acidmentioning
confidence: 99%
“…18.1. Relation between intracellular nitrogen and phosphorus ratios and toxin concentrations for the toxin-producing dinoflagellates Alexandrium tamarense and A. minutum (data from the NUTOX project, see Acknowledgements) and flagellates Prymnesium parvum and Chrysochromulina polylepis grown under different N and P conditions (data from Granéli 1999a, 1999b) For diarrhetic shellfish poisoning (DSP)-producing Prorocentrum lima, both N and P deficiency have been found to promote high okadaic acid (OA) toxin accumulations (McLachlan et al 1994and Sohet et al 1995, cited in Granéli et al 1998. For Dinophysis species, Johansson et al (1996) have shown that under N limitation, OA levels in D. acuminata cells increased (from 9 to 23 pg OA cell -1 ), whereas in D. acuta there was an increase in OA only when the cells were grown in sufficient conditions with a N:P atomic ratio of 16:1.…”
Section: Inorganic Nutrients and Toxin Contentmentioning
confidence: 99%